Immunogenic cell death unlocks the potential for combined radiation and immunotherapy - Somiya Rauf; Alexandra Smirnova; Andres Chang; Yuan Liu; Yi Jiang (Proceedings of the National Academy of Sciences, 2025)
Immunogenic cell death (ICD) enhances antitumor immunity by releasing tumor-associated antigens and activating the antitumor immune system response. Here, we develop a mathematical model to quantify the role of ICD in optimizing the efficacy of combined radiotherapy (RT) and macrophage-based immunotherapy. Using preclinical murine data targeting the SIRP α -CD47 checkpoint, we show that RT alone induces minimal ICD, whereas disrupting the SIRP α -CD47 axis significantly enhances both phagocytosis and systemic immune activation. Our model predicts an optimal RT dose (6 to 8 Gy) for maximizing ICD, a dose-dependent abscopal effect, and a hierarchy of treatment efficacy, with SIRP α -knockout macrophages exhibiting the strongest tumoricidal activity. These findings provide a quantitative framework for designing more effective combination therapies, leveraging ICD to enhance immune checkpoint inhibition and radiotherapy synergy.